Evaluation of sour cherry (Prunus cerasus L.) and European plum (Prunus domestica L.) varieties for making dried fruits - Simon, G.; Hegedűs, A.; Bulkai, Zs. (International Journal of Horticultural Science, 2007)
The aim of our drying trials was to determine the drying suitability of stone fruits. The tested species were sour and sweet cherries and European plums too. Data and results of sweet cherry drying were published earlier (Klincsek et. al. 2005, 2006).This article containing results of twenty sour cherry and six European plum varieties. Laboratory tests, drying processes and sensory testing were done at Fruit Quality Testing Laboratory of Fruit Science Department of Corvinus University of Budapest. The sensory tests and their valuations were done by the instruction of National Institute for Agricultural Quality Control. In the case of sour cherries by one year data in 2004 we divided fruits to five categories by suitability for making dried fruit. Varieties in the first two groups are the followings: most suggested for making dried, fruits: 'Meteor korai' and `Érdi jubileum'; suggested: 'IV-3-48' and `Piramis'.In the case of European plums three varieties can be suggested for making dried fruits from the six tested cultivars: ‘Révfülöpi’, Althann gage' and `Besztercei'.